2015
DOI: 10.3390/ijms161226166
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Cilostazol Nanoparticles Ameliorates Acute Ischemic Stroke in a Cerebral Ischemia/Reperfusion-Induced Injury Model

Abstract: It was reported that cilostazol (CLZ) suppressed disruption of the microvasculature in ischemic areas. In this study, we have designed novel injection formulations containing CLZ nanoparticles using 0.5% methylcellulose, 0.2% docusate sodium salt, and mill methods (CLZnano dispersion; particle size 81 ± 59 nm, mean ± S.D.), and investigated their toxicity and usefulness in a cerebral ischemia/reperfusion-induced injury model (MCAO/reperfusion mice). The pharmacokinetics of injections of CLZnano dispersions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
1
30
1
Order By: Relevance
“…Recently, Kasahara et al (25) reported that treatment with CLZ suppressed the disruption of the microvasculature in ischemic areas. In addition, we reported that the intravenous administration of CLZ attenuated brain damage when administered immediately after the onset of ischemic stroke symptoms in MCAO/reperfusion mice (15). From these findings, we investigated whether the oral administration of CLZ/R tablets prevented ischemic stroke in MCAO/reperfusion mice and found that CLZ/R nano tablets attenuated ischemic stroke (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, Kasahara et al (25) reported that treatment with CLZ suppressed the disruption of the microvasculature in ischemic areas. In addition, we reported that the intravenous administration of CLZ attenuated brain damage when administered immediately after the onset of ischemic stroke symptoms in MCAO/reperfusion mice (15). From these findings, we investigated whether the oral administration of CLZ/R tablets prevented ischemic stroke in MCAO/reperfusion mice and found that CLZ/R nano tablets attenuated ischemic stroke (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…We previously designed drug nanoparticles by the breakdown method using a ball and bead mill (13)(14)(15)(16)(17)(18) and showed that indomethacin solid nanoparticles enhanced drug bioavailability in the small intestine of rats (17). In this study, we designed new oral formulations containing CLZ solid nanoparticles using a combination of recrystallization and breakdown methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Solid drug nanoparticles come with the added benefits of possible cellular targeting and improvement in cellular uptake and have been used widely as nanotechnology-based delivery systems. We previously designed solid nanoparticles created by a breakdown method (bead mill), and reported on their low toxicity and high transdermal penetration via endocytosis when used in nano-formulations [12][13][14][15][16]. It is expected that the application of solid nanoparticles to the eyelid may be a possible route to sustained drug supplementation to the ocular surface and provide a novel strategy for ophthalmic DDS.…”
Section: Introductionmentioning
confidence: 99%